2018
DOI: 10.1007/s00590-018-2157-3
|View full text |Cite
|
Sign up to set email alerts
|

Posterior subdeltoid and external rotators preserving approach for reduction and fixation of displaced extra-articular fractures of the scapula

Abstract: Therapeutic study, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
6
0
4
Order By: Relevance
“…These patients had a mean adjusted age of 41.7 years (range 34-48.8) and a mean adjusted follow up time of 38.8 months, 253 were males and 85 females,138 were in right side and 125 in left side, as regard site of fracture mentioned in some studies were mainly in body (n.202), neck in (n.84) as shown Table 1. (9) 16 45.6 14\2 Right (n.9), left (n.7) Tatro et al (1) 37 45.4 29\8 93.6 ND Body (n.36), neck (n.1) Fandridis et al (10) 6 34 6\0 28 ND Yuan et al (11) 72 37.5 44\28 60.3 Right (n.40), left (n.32) Body Porcellini et al (12) 6 48.8 5\1 49.8 Right (n.2), left (n.4) Ao et al (13) 22 38 12\10 19.5 ND Schroder et al (2) 61 44 49\12 33 Right (n.27), left (n.34) Neck Lin et al (14) 13 38.7 6\7 24 Right (n.8), left (n.5) Jones et al (15) 31 42.6 27\4 Right (n.18), left (n.13) Body (n.12), neck (n.19) Cole et al (16) 5 44 3\2 39 Right (n.4), left (n.1) Bartoníček et al (5) 22…”
Section: Resultsunclassified
“…These patients had a mean adjusted age of 41.7 years (range 34-48.8) and a mean adjusted follow up time of 38.8 months, 253 were males and 85 females,138 were in right side and 125 in left side, as regard site of fracture mentioned in some studies were mainly in body (n.202), neck in (n.84) as shown Table 1. (9) 16 45.6 14\2 Right (n.9), left (n.7) Tatro et al (1) 37 45.4 29\8 93.6 ND Body (n.36), neck (n.1) Fandridis et al (10) 6 34 6\0 28 ND Yuan et al (11) 72 37.5 44\28 60.3 Right (n.40), left (n.32) Body Porcellini et al (12) 6 48.8 5\1 49.8 Right (n.2), left (n.4) Ao et al (13) 22 38 12\10 19.5 ND Schroder et al (2) 61 44 49\12 33 Right (n.27), left (n.34) Neck Lin et al (14) 13 38.7 6\7 24 Right (n.8), left (n.5) Jones et al (15) 31 42.6 27\4 Right (n.18), left (n.13) Body (n.12), neck (n.19) Cole et al (16) 5 44 3\2 39 Right (n.4), left (n.1) Bartoníček et al (5) 22…”
Section: Resultsunclassified
“…A DASH score between 0 and 29 is considered to be the point where the patient no longer considers their upper limb disorder is a problem (20). Past studies reported mean DASH score between 8.1 and 14 for all patients who underwent surgical interventions for scapular neck and body fractures (10,13,16,18,19,21). The patient-reported functional outcome using SF-36 questionnaire scored between 70 and 89.6 (comparable to normal healthy population 61 to 84), with exception to two subcategories, i.e., REE (role limitations due to emotional problems) and REP (role limitations due to physical health).…”
Section: Discussionmentioning
confidence: 99%
“…Bei diesem Zugang kann im Vergleich zu anderen weichteilschonender gearbeitet werden, und es wurden exzellente Ergebnisse beschrieben [37].…”
Section: Brodsky-zugangunclassified